Endometrial cancer in young women: prognostic factors and treatment outcomes in women aged ≤40 years. Issue 5 (25th March 2020) - Son, Ji; Carr, Caitlin; Yao, Meng; Radeva, Milena; Priyadarshini, Anju; Marquard, Jessica; Michener, Chad M; AlHilli, Mariam
Abstract : Objective: Endometrial cancer in pre-menopausal patients aged ≤40 years is rare and poses both diagnostic and management challenges. The goal of this study was to investigate the clinical and pathologic factors associated with endometrial cancer in this group and their impact on survival. Methods: Patients with endometrial cancer treated between January 2004 and August 2016 were retrospectively reviewed. Patients who underwent either primary surgical treatment or fertility-sparing therapy were included. Exclusion criteria were age >60 years and patients who received neoadjuvant chemotherapy or primary radiation. Age at diagnosis was used to classify patients into two groups: ≤40 and 41–60 years. Clinical and pathologic variables were compared between the groups. Progression-free survival and overall survival were estimated using Cox proportional hazards. Results: A total of 551 patients were evaluated, of which 103 (18.7%) patients were ≤40 years and 448 (81.3%) were 41–60 years. Age ≤40 years was associated with higher body mass index (38.8 vs 35.8 kg/m 2, p=0.008), non-invasive cancers (54.2% vs 32.6%, p<0.001), lower uterine segment involvement (27.2% vs 22.5%, p<0.001), and less lymphovascular space invasion (16.8% vs 29.1%, p=0.015). The rate of synchronous ovarian cancer was 9.2% vs 0.7% in age 41–60 years (p<0.001), and 19% of women with endometrial cancer aged ≤40 years underwent fertility-sparing therapy. Grade, stage, myometrial invasion, lymphovascular space invasion, and lymph node status were associated with survival, and fertility-sparing therapy adversely affected the recurrence rate of the age ≤40 years cohort. Among all patients aged ≤60 years, mismatch repair deficiency due to MLH1 methylation was associated with worse progression-free survival, 48.6% vs 83.3% (HR 1.98, 95% CI 1.06 to 3.17, p=0.032), and overall survival, 56.5% vs 90.0% (HR 2.58, 95% CI 1.13 to 5.90, p=0.025). Conclusions: Patients aged ≤40 years with endometrial cancer have more favorable prognostic factors and higher rates of synchronous tumors. Fertility-sparing therapy was associated with higher recurrence rates. The prognostic value of MLH1 methylation in this population warrants further investigation.